Single-Stage ZVS-PWM AC-AC Power Converter Using All SiC Power Module for High-Frequency Induction Heating Applications - Mishima, T.; Morinaga, S.; Nakaoka, M. (Institute of Electrical Engineers of Japan, 2016)
This paper presents a novel prototype of a single-stage zero voltage soft-switching (ZVS) pulse-width-mod ulation (PWM)-controlled AC-AC converter with a silicon carbide(SiC)-MOSFET/SiC-SBD power module for high frequency (HF) induction heating (IH) applications. The newly developed AC-AC converter can achieve higher efficiency than a Si-IGBT/Si-PNdiode power module-based prototype thanks to a low ON-resistance of SiC-MOSFET and a low forward voltage of SiC-SBD under the condition of high frequency switching. The performances of the new prototype converter are evaluated by experiment with a single-phase IH utensil of ferromagnetic stainless metal, after which the high-efficiency and low switching noise characteristics due to the all SiC power module are actually demonstrated.